The growth of fashion brands for trans bodies and their inclusive products (ModaPalavra e-periódico, 2025)
This article addresses the role of inclusive fashion in promoting diversity, with a specific focus on the needs of non-binary communities and trans people. The research aims to contextualize global transformations in the fashion industry, highlighting ethical, human and collaborative values. Therefore, practical examples of brands and entrepreneurs that contribute to this transformation are presented, highlighting the importance of dialogue and the direct involvement of diverse experiences in the creation process. The article also emphasizes the continued need to raise awareness about the invisibility of the transgender population and highlights fashion and design as significant agents in promoting social inclusion. The methodological approach adopted includes conducting a bibliographical review of several sources. Companies such as Transtore Binders and Trucss are referenced, which offer products such as binders, underwear, among others. The findings of this research indicate that inclusive fashion goes beyond a market approach, playing an essential role in promoting diversity and accepting diverse gender identities. LGBTQIAPN+ entrepreneurs have a positive impact on representation and identification in the commercial sector.
Keywords: social inclusion; inclusive clothing; gender identities